Comparison of particle bombardment-transformation parameters between stem and calli explants of Aglaonema simplex - Ma, Nyuk Ling; Cha, Thye San; Mahmood, Maziah; Ahmad, Aziz (Academic Journals, 2013)
Aquatic plant posses a very interesting stress tolerance mechanism compared to terrestrial plants. However, lack of aquatic mutants available is a hindrance to explore the cellular mechanism that governs various adaptations between these two types of plants. Therefore, the aim of this study is to provide the optimum parameters for the genetic transformation of native aquatic plant in tropical country, Aglaonema simplex, by using stem and callus tissue. Explants were bombarded with various sizes of gold particles coated with 35 sec promoter constructed into 35 sec-sGFP-TYG-nos (puc18) plasmid harbouring green fluorescent protein. High transient expression was obtained when the tissues were bombarded twice by gold particles coated with spermidine under acceleration pressure of 1100-1350 psi and with the vacuum pressure set to 24 Hg. The calli were found susceptible to high pressure impact, showing better result at a longer bombardment distance (12 cm) of stopping screen to explants by the use of gold particle of smaller size (1 μm). In contrast, the optimal bombardment distance shown by stem tissues was achieved at a 6 cm distance by the use of gold particle of 1.6 μm. PCR and PCR-southern blot analyses exhibited that the gene was integrated into the genome of transformants and this indicates that the protocol can be used for genetic engineering purpose in the future.